The efficiency and use of a reciprocating system aid for standing and walking in children affected by severe cerebral palsy - Avaltroni, Priscilla; Ivanenko, Yury; Assenza, Carla; Catania, Hilenia; Coluccini, Michele; Morone, Giovanni; Morelli, Daniela; Cappellini, Germana (Frontiers in Pediatrics, 2024)
Cerebral Palsy (CP) is a leading cause of childhood motor disability, making independent walking a crucial therapeutic goal. Robotic assistive devices offer potential to enhance mobility, promoting community engagement and quality of life. This is an observational report of 22 cases of children with CP in which we evaluated the Moonwalker exoskeleton (a dynamic moving aid system) usability, functional changes, and caregivers' perspectives based on the International Classification of Functioning (ICF). All children (aged 2-8 yrs, with a severe gait impairment and inability to use a conventional walker) underwent Moonwalker training for 20 sessions, followed by home use for five months. Post-treatment, majority of children showed improved endurance assessed by the 10meter walk test, with no negative effects on trunk control. Many of them achieved rather remarkable results reaching a velocity of ≥0.5 m/s given the constraints of the walking exoskeleton and the children's size, while at admission all children walked at a speed of less than 0.5 m/s. Several positive environmental factors and family adherence were noted, as assessed by ICF in a subgroup of children. This study on a sample of children demonstrated that the Moonwalker exoskeleton allows walking and training at home in children with severe CP, enhancing development, social interaction, and endurance, while being well-received by families.